Comparative Study of Various E. coli Strains for Biohydrogen Production Applying Response Surface Methodology - Péter Bakonyi; Nándor Nemestóthy; Katalin Bélafi-Bakó (The Scientific World Journal)
The proper strategy to establish efficient hydrogen-producing biosystems is the biochemical, physiological characterization of hydrogen-producing microbes followed by metabolic engineering in order to give extraordinary properties to the strains and, finally, bioprocess optimization to realize enhanced hydrogen fermentation capability. In present paper, it was aimed to show the utility both of strain engineering and process optimization through a comparative study of wild-type and genetically modified E. coli strains, where the effect of two major operational factors (substrate concentration and pH) on bioH2 production was investigated by experimental design and response surface methodology (RSM) was used to determine the suitable conditions in order to obtain maximum yields. The results revealed that by employing the genetically engineered E. coli (DJT 135) strain under optimized conditions (pH: 6.5; Formate conc.: 1.25 g/L), 0.63 mol H2/mol formate could be attained, which was 1.5 times higher compared to the wild-type E. coli (XL1-BLUE) that produced 0.42 mol H2/mol formate (pH: 6.4; Formate conc.: 1.3 g/L).